Global Shifts in Cardiovascular Disease, the Epidemiologic Transition, and Other Contributing Factors: Toward a New Practice of Global Health Cardiology - Mendoza W. (2017)
The epidemiologic transition theory, since it was first proposed, gave an intellectual boost to understanding the changing dynamics of epidemiologic profiles. The epidemiologic transition provided a complement to the discourse of demographic change. Despite its criticisms and revisions, it is still a useful concept that influences public health debates, and has proved to be influential, particularly in changing societies. Most countries are facing the rapidly emerging needs of populations